ANALISIS PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (Studi pada BPJS Kesehatan Cabang Utama Surakarta) - Ananda Putri, Dea; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2015)
Job satisfaction and organizational commitment affect employee performance. The purpose of this research is to explain how the variable of job satisfaction and organizational commitment influence to BPJS Kesehatan Cabang Utama Surakarta employee performance. In addition to recognize which variable influences dominantly to the employee performance.The data of this research were collected through a questionnaire distributed to 65 employees of BPJS Kesehatan Cabang Utama Surakarta. Mechanical testing of the data used in this research include the instrument test (validity and reliability test), classical assumption test (normality test, multicoloniarity, and heteroscedasticity test), multiple linear regression analysis, t test, F test, and coefficient of determination test (R2) using SPSS application.The result of this research shows that job satisfaction and organizational commitment influence positively and significantly to theemployee performance. Variable used in this research give positive response, meaning the job satisfaction and organizational commitment improving the performance of BPJS Kesehatan Cabang Utama Surakarta employee. Value of determination coefficient or R2 is 0,364, which means employee performance is affected by job satisfaction and organizational commitment amounted to 36,4%